Analysis of Public Opinion on Instagram Social Media on Convolutional Neural Network - arjuna prayoga satriongko; Muhammad Fauzan Alpri; Jonathannael Benerghes Putramasi; Supina Batubara (Yayasan Sinergi Multidimensi Kreatif, 2024)
This study investigates public opinion on Instagram social media regarding Convolutional Neural Networks (CNNs). Instagram has become a prominent platform for sharing opinions and content, making it crucial to understand how CNNs are perceived and discussed. The analysis utilizes sentiment analysis and content analysis techniques to gauge the sentiments and topics surrounding CNN discussions on Instagram. Findings reveal the dominant sentiments and prevalent themes in public discourse, shedding light on the broader perceptions and understanding of CNN technology within the Instagram community.